АNALYSIS OF PSYCHOTROPIC DRUG CONSUPTION FOR SCHIZOPHRENIA TREATMENT IN DIFFERENT TYPE HOSPITALS - P. S. Nosova; O. V. Reshetko (IRBIS LLC, 2015)
the goal of our research was to carry out an analysis of psychotropic drug utilization used for patients with schizophrenia in two (state and municipal) in-patient clinics during 2000 and 2010, using the DDD methodology. As the result, we found out that psychotropic drug utilization increased from 2000 to 2010 in both types of in-patient clinics. Consumption of second-generation antipsychotics increase in state clinic in 2010. And in the state clinic we can observe a favorable trend in the decrease of antidepressants and tranquilizers consumption.